Mutational activation of the β-Catenin proto-oncogene is a common event in the development of Wilms’ tumors - Koesters, Robert; Ridder, Rüdiger; Kopp-Schneider, Annette; Betts, David; Adams, Volker; Niggli, Felix; Briner, Jakob; Knebel Doeberitz, Magnus von (Cancer research, 1999)
Activation of β-catenin-mediated transcription is the nuclear end point of organ-specific Wnt signaling. In the developing kidney, Wnt-4, a secreted glycoprotein, acts as an autoinducer of the mesenchymal to epithelial transition that underlies normal nephron development. Dysregulation of this epithelial transformation process may lead to Wilms’ tumors (WTs). In this study, we investigated the potential role of the β-catenin proto-oncogene, a candidate downstream target molecule of Wnt-4 signaling, in the development of WTs. In 6 of 40 tumors (15%), mutation analysis revealed heterozygous missense mutations or small deletions that result in the loss of important regulatory phosphorylation sites within the β-catenin protein. These findings indicate that activating β-catenin mutations may play a significant role in the development of WTs and establish a direct link between Wilms’ tumorigenesis and the Wnt signal transduction pathway governing normal kidney development.
Gesehen am 19.10.2020